Institutionalization of Public-Private Partnership: Global Experiences and the Basic Outlines of a Proposal for Slovenia - Mojmir Mrak (Central European Public Administration Review)
Experiences show that countries use one of the following three forms for “institutionalisation” of their private-public partnership (PPP) activities: (i) centralised, (ii) decentralised, and (iii) mixed. The article argues that the form of mixed PPP “institutionalisation” would be the most appropriate for Slovenia. The institutional structure would be composed of three institutions: (i) central PPP unit responsible, first, for horizontal coordination of all PPP policies in the country, and second, for implementation of PPP projects in all those areas where sectoral PPP units would not be created, (ii) very limited number of sectoral PPP units (probably 1 to 2) that would be responsible for implementation of PPP projects in their respective sectors, and (iii) advisory board that would advise the central PPP unit in designing the most complex segments of the PPP policies in the country and would provide a platform for professional discussion and for communication with the public at large on a wide variety of PPP issues. In substance terms, the central PPP unit would be responsible directly to the government while in organisational terms, it would be incorporated into the institutional structure of the ministry of finance with the head of the unit being directly responsible to the minister of finance.